Handling operations to reduce post-harvest losses in mango - Negi, Taru; Sharma, Satish Kumar; Kumar, Anil (Indian Farming, 2023)
Mango fruit is largely like by peoples and it contains a good amount of vitamins, minerals and antioxidants. India is the largest producer and an important, exporter of mango in the world. It is observed that around 25–45% of post-harvest losses occurs in mango, that can be successfully reduced by following proper post-harvest handling operations, which includes; trimming, desapping, sanitization, grading, hot water treatment, waxing etc. Mango is usually harvested when fully matured, but in the unripe stage; as it is highly perishable in nature it can be artificially ripened at the destination market before sale. Plastic crate, wooden boxes and corrugated fiberboard can be used for packaging of mangoes that can be transported in refrigerated vehicles to decrease the post-harvest losses.